Error Analysis of the Use of Simple Past Tense in English Narrative Essays of Grade VIII Students of SMP Negeri 76 Jakarta - Syauqiyah, Syifa; Prasetyo, Agung (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2025)
The purpose of this study is to identify various types of errors made by students of SMP Negeri 76 Jakarta class VIII in making narrative essays and to identify the most dominant types of errors that are often done by students when composing narrative essays. The research approach used in this study is a qualitative approach with descriptive method. After analyzing the errors made by students, the author can draw a conclusion The type of error in using simple past tense most often made by students is misformation (formation error), with a percentage of 73.04%. This error consists of 84 errors out of a total of 115 errors. On the other hand, the least frequent type of verb usage error made by students is misordering, with a percentage of 5.21%, or only 6 errors out of a total of 115. In addition, students also made other errors, such as addition errors at 6.08%, which included 7 errors out of a total of 115, and errors of omission at 15.65%, with a total of 18 errors out of a total of 115.